2014
DOI: 10.1098/rspb.2013.2511
|View full text |Cite
|
Sign up to set email alerts
|

Sociality influences cultural complexity

Abstract: Archaeological and ethnohistorical evidence suggests a link between a population's size and structure, and the diversity or sophistication of its toolkits or technologies. Addressing these patterns, several evolutionary models predict that both the size and social interconnectedness of populations can contribute to the complexity of its cultural repertoire. Some models also predict that a sudden loss of sociality or of population will result in subsequent losses of useful skills/technologies. Here, we test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
179
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(193 citation statements)
references
References 38 publications
(51 reference statements)
13
179
0
1
Order By: Relevance
“…Large interaction networks allow individuals to learn from many others, and theory predicts that increased opportunities to learn socially reduces the rate of cultural loss and increases the rate at which people improve existing cultural traits. This prediction is supported by evidence from both field and laboratory studies (5)(6)(7)(8)(9)(10). However, some authors have been reluctant to embrace this idea, pointing out discrepancies between measures of population size and observed cultural complexity (11)(12)(13)(14).…”
supporting
confidence: 51%
“…Large interaction networks allow individuals to learn from many others, and theory predicts that increased opportunities to learn socially reduces the rate of cultural loss and increases the rate at which people improve existing cultural traits. This prediction is supported by evidence from both field and laboratory studies (5)(6)(7)(8)(9)(10). However, some authors have been reluctant to embrace this idea, pointing out discrepancies between measures of population size and observed cultural complexity (11)(12)(13)(14).…”
supporting
confidence: 51%
“…payoff-biased social learning), but large-scale archaeological studies such as Powell et al (2009) can only test the outcome of this model, not the validity of the mechanisms. Derex et al (2013), Muthukrishna et al (2014) and all found that, as predicted, larger groups containing more individuals from whom to learn supported higher levels of cultural complexity in various tasks, including designing computerised fishing nets, knottying, and completing jigsaw puzzles. While Derex et al (2013) and Muthukrishna et al (2014) showed that Henrich's (2004) payoff-biased mechanism works, showed that the effect can also be seen when people integrate the solutions of other people into a single solution (a kind of 'blending inheritance').…”
Section: Demography Can Influence the Evolution Of Cultural Complexitymentioning
confidence: 99%
“…Derex et al (2013), Muthukrishna et al (2014) and all found that, as predicted, larger groups containing more individuals from whom to learn supported higher levels of cultural complexity in various tasks, including designing computerised fishing nets, knottying, and completing jigsaw puzzles. While Derex et al (2013) and Muthukrishna et al (2014) showed that Henrich's (2004) payoff-biased mechanism works, showed that the effect can also be seen when people integrate the solutions of other people into a single solution (a kind of 'blending inheritance'). Further work is needed to delineate the precise micro-evolutionary mechanisms that support the macroevolutionary link between population size and cultural complexity.…”
Section: Demography Can Influence the Evolution Of Cultural Complexitymentioning
confidence: 99%
“…The new approach at L2 was then copied by other children, to become a shared innovation. This was repeated at L3 but almost exclusively the cognitive resources shared in the group condition as those of a 'collective brain' [3,42], an expression apt to the contrast between the progressive innovations of the children in our groups, compared to the asocial condition. We suggest there is much scope here for linkage with recently expanding research on collective cognition in animal groups [59,60].…”
Section: (A) Defining and Identifying Invention Innovation Social Lmentioning
confidence: 99%
“…However, it has become common to apply more demanding definitions that also bring in the other, 'copying' engine, for example defining the process of behavioural innovation as one that 'results in new or modified learned behaviour and that introduces novel behavioural variants into a population's despite its significance for human culture, experimental investigation of the cumulative aspect began only recently in humans [32] and in chimpanzees [33]. The human studies began with 'laboratory micro-cultures' such as building spaghetti-and-plasticine towers as high as possible [34,35], later investigating the social learning processes necessary for transmission [35][36][37] and factors moderating cultural fidelity, conformity and diversity [38][39][40][41][42]. Allied approaches have been applied to the evolution of artificial 'mini-languages' in humans and non-humans [43,44], although here the 'cumulative' effect is typically not the creation of more complex outcomes, but a regularization of the transmitted 'syntax' that is increasingly memorable and replicable.…”
Section: A Note On Terminologymentioning
confidence: 99%